AKUPUNTUR SEBAGAI TERAPI ADJUVAN PADA PASIEN DEPRESI BERAT (Case Report) - Rachmadian, Okky Dita; Herdaetha, Andriesti; Oktaviyantini, Tri (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Based on WHO data, almost 20%-30% of hospital patients in developing countries experience mental emotional disorders such as depression. Depression occurs from mild to severe, thus interfering with daily functioning. The most effective therapy for severe depression is electroconvulsant therapy (ECT). But in some cases it cannot be done, so there needs to be alternative therapies. Acupuncture can trigger endorphins and lower cortisol levels that can affect a person's mood. In this case, we present A 50-year-old woman with a diagnosis of recurrent depressive disorder now severe episodes with psychotic symptoms was planned to receive ECT therapy, but the patient was not eligible. Then the patient is given drugs Fluoxetine 1x20 mg and Clozapine 1x50 mg. The patient is still silent, neither eating nor answering questions. Based on several journals found, acupuncture can be given as an additional therapy given with psychopharmaceuticals. Acupuncture is beneficial in faster improvement of depressive symptoms when compared to patients who only get antidepressants. After several acupuncture sessions, patient’s symptomps was improved. So we conclude that acupuncture can be used as an additional therapeutic option given together with psychopharmaceuticals to depressed patient.